Activist conceptualisations at the migration-welfare nexus: Racial capitalism, austerity and the hostile environment. (August 2021) - Vickers, Tom
In recent years British welfare policy and immigration policy have intertwined in new ways, with widespread cuts alongside increasing conditionality, rationing, and differentiation of rights. This article explores perspectives among activists attempting to resist these developments, with a focus on those that go beyond narrow reactions and engage in systemic critiques. It draws on in-depth qualitative interviews with activists from a variety of campaigns in England. The article presents a conceptual framework, synthesising these activists' ideas and comprising three elements: racialised profit-seeking as a driver of policy; 'situated universalism' as a counter-hegemonic basis for unity; and a theory of change through grassroots campaigns.